2020
DOI: 10.3847/1538-4357/ab86bd
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence for the Origin of High-energy Neutrinos in Parsec-scale Nuclei of Radio-bright Active Galaxies

Abstract: Observational information on high-energy astrophysical neutrinos is being continuously collected by the IceCube observatory. However, the sources of the neutrinos are still unknown. In this study, we use radio very long baseline interferometry (VLBI) data for a complete VLBI flux density–limited sample of active galactic nuclei (AGNs). We address the problem of the origin of astrophysical neutrinos with energies above 200 TeV in a statistical manner. It is found that AGNs positionally associated with IceCube e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
281
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(300 citation statements)
references
References 106 publications
15
281
4
Order By: Relevance
“…There is also some level of uncertainty in the detector systematic uncertainties and therefore in the reconstruction errors, which is why we use the published upper limit of 1.0 • (IceCube Collaboration 2013) in our analysis. However, following Plavin et al (2020a), we estimate the optimal systematic uncertainty using our data (see Sect. 3).…”
Section: Neutrino Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also some level of uncertainty in the detector systematic uncertainties and therefore in the reconstruction errors, which is why we use the published upper limit of 1.0 • (IceCube Collaboration 2013) in our analysis. However, following Plavin et al (2020a), we estimate the optimal systematic uncertainty using our data (see Sect. 3).…”
Section: Neutrino Eventsmentioning
confidence: 99%
“…Kadler et al (2016) discovered PKS B1424−418 flaring in the radio and γ-ray bands in temporal and positional coincidence with the IceCube neutrino IC35, but this neutrino event had a large positional error circle of 15.6 • . The first systematic search of radio sources was performed only recently, by Plavin et al (2020a), who investigated the association of neutrinos with radio bright AGNs using the VLBI based radio fundamental catalogue (RFC) 1 and RATAN-600 (Korolkov & Pariiskii 1979) data. They found that AGNs positionally associated with high-energy IceCube events typically have stronger parsec-scale cores compared to the rest of the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although acceleration is carried out equally for both protons and electrons, due to the more intense synchrotron radiation, the electrons lose a significant energy, which prevents them from reaching maximum energy. According to IceCube results (Plavin 2020), the neutrino energy in the sub-parsec region at the base of the jet corresponds to the energy of colliding protons E p ≃ 10 16 − 10 17 eV, which corresponds to orders of magnitude energy acquired by protons in the region of the SMBH magnetosphere. The simulation uses a kinetic approach to describe the motion of a particle.…”
Section: Introductionmentioning
confidence: 99%
“…The recent point source search with 10 year data of IceCube track-like events indicate 3.3 inconsistency with background for the full Nothern Hemisphere source catalog [6]. Moreover recent studies indicate 4.1 association of IceCube track-like events with radio-bright blazars selected on the basis of very long baseline interferometry observations [7].…”
Section: Introductionmentioning
confidence: 99%